Penyuluhan dengan Media Video Edukasi Meningkatkan Pengetahuan Pemberantasan Sarang Nyamuk Demam Berdarah Dengue Pada Siswa Sekolah Dasar: Counseling Using Educational Video Media To Improve Knowledge On Dengue Hemorrhagic Fever Mosquito Breeding Site Eradication Among Elementary School Students. - Luh Putu Nita Damayanti; I Wayan Sudiadnyana; Anysiah Elly Yulianti (Poltekkes Kemenkes Denpasar, 2026)
Title: Counseling Using Educational Video Media To Improve Knowledge On Dengue Hemorrhagic Fever Mosquito Breeding Site Eradication Among Elementary School Students Background: SD Negeri 1 Kamasan is located in a densely populated area, making it a potential breeding ground for mosquitoes. Additionally, no previous educational outreach has been conducted regarding the eradication of Dengue Hemorrhagic Fever (DHF) mosquito breeding sites. This study aims to determine whether counseling through educational video media can improve students’ knowledge about eradicating mosquito breeding sites associated with DHF at SD Negeri 1 Kamasan. Method: This study employed a Pre-Experimental Design with the One-Group Pretest-Posttest Design method. Statistical analysis included the Kolmogorov-Smirnov normality test and the Paired t-test. Result: The average knowledge score before the intervention was 62.47, while the average score after the intervention was 91.14. The Paired t-test results showed a p-value of 0.000 (< 0.05), indicating a statistically significant difference in knowledge before and after the intervention. Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Conclusion: There is a difference in knowledge before and after the counseling on eradicating Aedes aegypti mosquito breeding sites using educational video media among students of SD Negeri 1 Kamasan.